(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article explores how interactive game technologies can be used as a pedagogical mechanism for cultivating early career awareness and age-appropriate vocational orientation among preschool children in higher-education and teacher-training contexts. In preschool education, “career awareness” is not understood as premature professional choice, but as the formation of foundational representations about social roles, work processes, tools, services, and the value of labor. The paper argues that interactive game technologies—digital and non-digital—create structured, motivating environments where children can safely simulate adult activities, practice communication and problem-solving, and internalize respectful attitudes toward different occupations. The study conceptualizes interactive games as a didactic system that unites play scenarios, role distribution, media and manipulatives, feedback loops, and reflective dialogue, enabling the educator to transform spontaneous role play into an educationally managed experience. The article proposes a methodological model for pedagogical universities: designing profession-themed interactive game modules aligned with preschool developmental tasks; embedding inclusive and gender-sensitive role narratives; integrating local cultural contexts and community occupations; and applying observation-based assessment tools to capture changes in children’s vocabulary,research-informed framework for future preschool teachers to implement interactive game technologies ethically and effectively, strengthening early socialization and preparing children for later stages of career exploration without reducing childhood to utilitarian training. social-role comprehension, cooperation, and motivation to explore. The expected contribution is a practical,